What has the Charter of Fundamental Rights of the European Union delivered for workers? - Dorssemont, Filip; Lörcher, Klaus; Clauwaert, Stefan; Schmitt, Mélanie (Brussels, 2019)
"This policy brief assesses the impact of the European Union’s Charter of Fundamental Rights, ten years on. The Charter is intended to guide EU institutions, particularly the CJEU, in recognising and promoting the social rights of EU citizens and workers. The briefing, which is based on a book-length project by the authors, analyses how the Charter has actually been used the EU institutions in their legal and political actions. Overall, the conclusion is that the Charter has not been promoted effectively enough and, indeed, has been deployed by the CJEU to block a more progressive interpretation of EU Directives. A number of hurdles therefore still need to be overcome in order for the Charter to live up to expectations."